Imperial republics : revolution, war, and territorial expansion from the English Civil War to the French Revolution - Andrew, Edward (Toronto : University of Toronto Press, 2011)
"Republicanism and imperialism are typically understood to be located at opposite ends of the political spectrum. In Imperial Republics, Edward G. Andrew challenges the supposed incompatibility of these theories with regard to seventeenth- and eighteenth-century revolutions in England, the United States, and France.
Many scholars have noted the influence of the Roman state on the ideology of republican revolutionaries, especially in the model it provided for transforming subordinate subjects into autonomous citizens. Andrew finds an equally important parallel between Rome's expansionary dynamic - in contrast to that of Athens, Sparta, or Carthage - and the imperial rivalries that emerged between the United States, France, and England in the age of revolutions. Imperial Republics is a sophisticated, wide-ranging examination of the intellectual origins of republican movements, and explains why revolutionaries felt the need to 'don the toga' in laying the foundation for their own uprisings."--pub. desc.
Rome in the Eighteenth Century. -- Chapter One. Machiavelli in the Eighteenth Century. -- Chapter Two. Republicanism in the English Civil War. -- Chapter Three. Catonic Virtue, Sweet Commerce and Imperial Rivalry. -- Chapter Four. Colony to Nation to Empire. -- Chapter Five. Caesar to Brutus to Augustus. -- Chapter Six. Le Royaume and la Patrie; France in the Eighteenth Century. -- Chapter Seven. The Role of Brutus in the French Revolution. -- Chapter Eight. Imperial Pride and Anxiety: Gibbon's Roman Empire and Ferguson's Roman Republic.
Includes bibliographical references and index.
Includes some text in French.
Keywords: 1600-luku; 1700-luku; 1789-1799; Imperialism; Political science -- Rome -- History; Republicanism -- Rome -- History; historia; imperialismi; Ranskan suuri vallankumous; sotahistoria; tasavaltalaisuus; vallankumoukset; valtio-oppi; France -- History -- Revolution, 1789-1799.; France -- Intellectual life -- 18th century; Great Britain -- History -- Civil War, 1642-1649.; Great Britain -- Intellectual life -- 17th century; United States -- History -- Revolution, 1775-1783.; United States -- Intellectual life -- 18th century; Iso-Britannia; Ranska; Rooman valtakunta; Yhdysvallat